(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2019)
the use of crumb rubber modifiers by dry process is not used extensively in asphalt applications as the wet process. This study aims to investigate the effect of crumb rubber modifiers on properties and performance of asphalt mix by dry process. Thus, a set of asphalt mixtures containing various percentages of crumb rubber modifiers mixed by the dry process were tested. Moreover, the effect of modifying conventional asphalt mixture with crumb rubber polymers was evaluated. In addition, a comparative assessment was made to evaluate rubberized mixtures and unmodified bitumen mixture. The mixtures were assessed by using the Marshall Stability test, the wheel tracking test and the moisture susceptibility test. The study revealed that an addition of crumb rubber modifiers to conventional asphalt mixture enhances pavement stability and increases its resistance to rutting and moisture damage. The study concludes that an addition of 2% of CR to unmodified AC16 gives the most satisfactory results among other rubberized mixtures.